Reframing Hope: The Process of Adapting Mothers to Children with Down Syndrome after Receiving a Diagnosis - Haerani Nur; Rohmah Rifani; Nurfitriany Fakhri (Journal of Educational, Health and Community Psychology, 2024)
This study aims to explore the experiences of mothers adapting after receiving a Down Syndrome (DS) diagnosis for their child. Utilizing a Heideggerian phenomenological approach, data was collected through in-depth interviews with 10 mothers of children with DS, focusing on their emotional responses, acceptance, and hopes. The analysis identified three main themes: initial reactions to the diagnosis and the resulting loss of hope, the process of acceptance, and managing hopes while adapting to the child's condition. The findings reveal the complex journey mothers undergo in restructuring their emotions and thoughts, underscoring the importance of diagnostic confirmation, social support, and spiritual beliefs in the acceptance process. This study contributes to a deeper understanding of mothers’ experiences following a DS diagnosis and offers insights for health professionals and support systems to better assist families during this critical period. The theme of “reframing hopes” emerged as central, facilitating mothers’ ability to adjust and maintain hope for their children’s futures.